2007
DOI: 10.1002/ibd.20084
|View full text |Cite
|
Sign up to set email alerts
|

Patchy distribution of mucosal lesions in ileal Crohnʼs disease is not linked to differences in the dominant mucosa-associated bacteria

Abstract: The dominant MAB do not differ between noninflamed and inflamed ileal mucosa in Crohn's disease. This argues against a localized dysbiosis to explain the patchy distribution of mucosal lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 36 publications
5
32
1
1
Order By: Relevance
“…We and others have shown that the composition of the dominant flora of the mucus layer is constant (high similarity index) along the colon in patients with CD, as well as in healthy subjects [38,40] . We were also unable to find significant differences between the microbiota present over an area of intestinal ulceration and in uninvolved mucosa in patients with CD or UC [41,42] . We did not find a microbial signal in the crypt abscesses of patients (although there are such signals in crypts and crypt abscesses from patients with infectious colitides [43] ).…”
Section: Mucosa-adherent Microbiotamentioning
confidence: 57%
“…We and others have shown that the composition of the dominant flora of the mucus layer is constant (high similarity index) along the colon in patients with CD, as well as in healthy subjects [38,40] . We were also unable to find significant differences between the microbiota present over an area of intestinal ulceration and in uninvolved mucosa in patients with CD or UC [41,42] . We did not find a microbial signal in the crypt abscesses of patients (although there are such signals in crypts and crypt abscesses from patients with infectious colitides [43] ).…”
Section: Mucosa-adherent Microbiotamentioning
confidence: 57%
“…No difference has been found in inflamed versus noninflamed tissue in CD and/or UC using DGGE, 152,222,228 TGGE, 229,230 FISH, 230 and clone library analysis. 138,149 A microarray study of samples from the same patient showed a similar profile whether from inflamed or noninflamed tissue.…”
Section: Inflamed Versus Noninflamed Mucosamentioning
confidence: 87%
“…Surgical samples and mucosal biopsy samples were processed directly in the operating room as previously described (27).…”
Section: Methodsmentioning
confidence: 99%